How to coexist with the 'killer shrimp' Dikerogammarus villosus? Lessons from other invasive Ponto‐Caspian peracarids. Issue 6 (8th November 2018) - Borza, Péter; Huber, Thomas; Leitner, Patrick; Remund, Nadine; Graf, Wolfram
Abstract: Studying interactions among co‐evolved invaders might help us in understanding, predicting, and perhaps mitigating the impact of the invading species on the native biota. The factors of spatial niche differentiation were investigated among invasive Ponto‐Caspian peracarids with the aim of revealing how co‐evolved species can coexist with the 'killer shrimp' Dikerogammarus villosus, an invasive gammarid replacing non‐Ponto‐Caspian species throughout Europe. Multi‐habitat samples from the third Joint Danube Survey were analysed by partitioning the variation in species density data between environmental and spatial explanatory variable sets. Relevant predictors were identified by forward selection and their role was interpreted based on the redundancy analysis (RDA) triplot. The effect of substrate types was further analysed in certain species using generalized linear models. The analysis revealed characteristic differences in habitat preference (i.e. spatial niche differentiation) among the species, allowing coexistence with D. villosus at different spatial scales. The relatively small and lean body of Chaetogammarus ischnus and Jaera sarsi might allow the avoidance of interference with large Dikerogammarus specimens by using narrow interstices among pebbles and stones (microhabitat‐scale differentiation). The remaining Ponto‐Caspian species included in the analysis showed an affinity for substrate types ( Obesogammarus obesus ) or current velocity intervals ( Dikerogammarus bispinosus ) that differed from those preferred by D. villosus (mesohabitat‐scale differentiation), presumably in connection with feeding preferences in some cases ( Dikerogammarus haemobaphes and Trichogammarus trichiatus ). These results provide a framework for a preliminary risk assessment concerning the continuing high potential for range expansion of D. villosus : i.e. the identification of the most vulnerable species in those regions of the world not invaded at present but potentially colonizable, based on their habitat preference and morphology. The lessons learned from Ponto‐Caspian peracarids can be applied to the whole macroinvertebrate fauna, as the same principles (i.e. the avoidance of interference) can be expected to determine their coexistence with D. villosus .